Populism and health inequality in high-income countries - Martin Lindström (Elsevier, 2020)
The rise of populist parties and movements in general and right-wing populist parties in particular has been noted also in the public health literature. While economic and other factors behind the populist surge have been systematically analyzed in the political and social science literature, the understanding of this political phenomenon seems weak in important parts of the public health literature. The lack of analysis of economic effects on health inequity of immigration of people with low levels of work skills to many high-income countries is given with the WHO Commission on Social Determinants of Health report as an example. Public health scholars should be able to fully analyze all effects on health inequity within countries. Public health scholars and professionals may lose credibility if they do not fully assess all relevant determinants, and the investigation of health inequity within countries should consider all systemic roots. Health inequity between countries is a crucial issue and should be addressed through international cooperation between countries, regions and international organizations. The approach from political science and social science should be adopted.